(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze the impact of Covid-19 on the lives of students of the Dentistry course at the University of Itaúna in the period 2020 and 2022 through a Google Forms questionnaire. The population consisted of students enrolled regularly, from the sixth to the tenth period, of the Dentistry course at the University of Itaúna. And excluded students were those students who were not regularly enrolled in the periods surveyed. The data obtained was tabulated by Google Forms and the analyzes were made from the generated graphs. The results showed that all students involved in the research took the vaccine against Covid-19, with 41(61,2%) taking up to the 3rd dose and 26(38,8%) up to the 2nd dose. Regarding the biosecurity measures adopted at the clinics at the University of Itaúna, 39(58,2%) thought they were effective in reducing the spread and contagion of the virus and 26(38,8%) agreed with parts of the measures. 65(97%) of the students considered that there was an increase in the levels of anxiety, stress and uncertainties related to the future. In addition, it is possible to note through the study that the pandemic affected the lives of dental students in many aspects, whether these are linked to the quality of learning as to the psychological state of the student, given that the growth in the rates of people with stress and anxiety in a pandemic moment facing an uncertain future.